Analysis of the influencing factors and predictive values for 30- day mortality in emergency severely ill patients - LIU Hongxin; WU Xiaojuan; MENG Jian (Yixue xinzhi zazhi)
Objective To study the influencing factors of 30 d mortality in emergency severely ill patients and the correlation between D-dimer, neutrophil to lymphocyte ratio (NLR), and early death in emergency severely ill patients.Methods The clinical data of severely ill patients admitted to Cangzhou People's Hospital from December 2015 to December 2020, including clinical biochemical indicator, sequential organ failure assessment (SOFA) score, acute physiology and chronic health evaluation II (APACHE II) score within 24 hours of admission were collected. According to the 30 d prognosis, the patients were separated into the survival group and the death group. Logistic regression was performed to analyze the risk factors for 30 d death in severely ill patients. The receiver operating characteristic (ROC) curve was performed to evaluate the predictive value of SOFA score, APACHE II score, D-dimer and NLR on 30 d death in severely ill patients.Results 1 595 severely ill patients were included, with 1 359 in the survival group and 236 in the death group. Compared with the survival group, the death group had higher fibrinogen, prothrombin time, white blood cell count, neutrophil count, NLR, platelet count, blood lactate, D-dimer level, SOFA score and APACHE II score and lower lymphocyte count (P